(untitled) (Harmoni, 2015)
This study employs qualitative approach that aims to find out the facts about the closing of seven churches conducted by Cianjur government and it evokes some reactions from Cianjur church organization (BKSAG) by reporting that case to national comission on human rights (Komnas HAM). The study shows that the church is not the real church like the ideal church but the shopping building and houses as residential areas are used as worship houses. Those churches are banned and closed by civil service police unit (Satpol PP) because they do not have a building permit. This study also explores the different understanding on PBM 2006 about the requirements to build worship houses and late local government response to that case that occurs for long time.